2007
DOI: 10.1016/j.cardiores.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 activates Stat3 in neonatal rat ventricular cardiomyocytes: A role in cardiac hypertrophy

Abstract: In ventricular cardiomyocytes, PGE2 induces the activation of Stat3 which plays an essential role in PGE2-induced increase in cell size and protein synthesis. The activation of Stat3 occurs mainly through EP4 and involves ERK1/2 as well as newly synthesized protein(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 39 publications
7
56
0
Order By: Relevance
“…Previous studies have shown that MEK and JNK pathways mainly induce Stat3 serine phosphorylation, which is required for transcriptional activities of Stat3 (36). Other studies also reported that Erk1/2 is indirectly involved in tyrosine Stat3 phosphorylation in cardiomyocytes (37,38). Interestingly, the current investigation observed many similarities, including delayed kinetics of Stat3 activation and involvement of de novo protein synthesis.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that MEK and JNK pathways mainly induce Stat3 serine phosphorylation, which is required for transcriptional activities of Stat3 (36). Other studies also reported that Erk1/2 is indirectly involved in tyrosine Stat3 phosphorylation in cardiomyocytes (37,38). Interestingly, the current investigation observed many similarities, including delayed kinetics of Stat3 activation and involvement of de novo protein synthesis.…”
Section: Discussionsupporting
confidence: 60%
“…STAT3 can be activated by IL-6, IL-10 or VEGF; adenosine can mediate STAT3 activation via IL-10, as demonstrated in mouse macrophages, 38 while PGE 2 itself has also been shown to phosphorylate STAT3 in cardiomyocytes. 39 Signaling via STAT3 can upregulate CD73 in Th17 cells. 10 However, when STAT3 was blocked in our model, instead of inhibition of CD73 upregulation, we observed significantly enhanced CD73 expression.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, IL-6 and Stat-3 are involved in hypertrophy and protection from ischemic injury. 23 To investigate a potential mechanism underlying the effect of cardiac myocyte-specific EP 4 deletion on cardiac hypertrophy, we performed Western blot for phosphorylated Stat-3.…”
Section: Effect Of Ep 4 Deletion On Activation Of Stat-3mentioning
confidence: 99%
“…4 It also increased protein synthesis, cell size, and brain or B-type natriuretic peptide (BNP) expression in cardiac myocytes, all markers of hypertrophic growth. 5,6 We have also shown that myocardial infarction (MI) increased generation of PGE 2 accompanied by upregulation of COX-2 in the mouse heart, and treatment with a specific COX-2 inhibitor for 2 weeks improved cardiac function and reduced hypertrophy and fibrosis. 7 Given that COX-2 products have both deleterious and protective effects in the heart and vasculature, 8 -10 it is important to understand how PGE 2 affects the prohypertrophic response.…”
mentioning
confidence: 99%